Characterization of Porous, Dexamethasone-Releasing Polyurethane Coatings for Glucose Sensors - Vallejo-Heligon, Suzana G. (2014)
Commercially available implantable needle-type glucose sensors for diabetes management are robust analytically but can be unreliable clinically primarily due to tissue-sensor interactions. Here, we present the physical, drug release, and bioactivity characterization of tubular, porous dexamethasone (Dex) releasing polyurethane coatings designed to attenuate local inflammation in the tissue-sensor interface. Porous polyurethane coatings were produced by the salt-leaching/gas-foaming method. Scanning electron microscopy (SEM) and Micro-computed tomography (Micro-CT) showed a controlled porosity and coating thickness. In vitro drug release from coatings monitored over two weeks presented an initial fast release followed by a slower release. Total release from coatings was highly dependent on initial drug loading amount. Functional in vitro testing of glucose sensors deployed with porous coatings against glucose standards demonstrated that highly porous coatings minimally affected signal strength and response rate. Bioactivity of the released drug was determined by monitoring Dex-mediated, dose-dependent apoptosis of human peripheral blood derived monocytes in culture. Acute animal studies were used to determine the appropriate Dex payload for the implanted porous coatings. Pilot short-term animal studies showed that Dex released from porous coatings implanted in rat subcutis attenuated the initial inflammatory response to sensor implantation. These results suggest that deploying sensors with the porous, Dex-releasing coatings is a promising strategy to improve glucose sensor performance.